2020
DOI: 10.1016/j.concog.2020.102899
|View full text |Cite
|
Sign up to set email alerts
|

Percolating ideas: The effects of caffeine on creative thinking and problem solving

Abstract: Caffeine is the most widely consumed psychotropic drug in the world, with numerous studies documenting the effects of caffeine on people's alertness, vigilance, mood, concentration, and attentional focus. The effects of caffeine on creative thinking, however, remain unknown. In a randomized placebo-controlled between-subject double-blind design the present study investigated the effect of moderate caffeine consumption on creative problem solving (i.e., convergent thinking) and creative idea generation (i.e., d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Green intellectual competence that is relevant for exploring novel pathways for generating green creative ideas to solve problems associated with green initiatives (Mack & Landau, 2015;Zabelina & Silvia, 2020) Green expertise The combination of green factual knowledge, technical aptitudes, and talents of a team (Chang & Chang, 2017;Tabesh et al, 2019) Green task motivation A strong interest inspired by strong challenge or satisfaction, curiosity or intention to accomplish fixed goals for green oriented tasks (Amabile, 1997;Birdi et al, 2016).…”
Section: Green Creativity Skillsmentioning
confidence: 99%
“…Green intellectual competence that is relevant for exploring novel pathways for generating green creative ideas to solve problems associated with green initiatives (Mack & Landau, 2015;Zabelina & Silvia, 2020) Green expertise The combination of green factual knowledge, technical aptitudes, and talents of a team (Chang & Chang, 2017;Tabesh et al, 2019) Green task motivation A strong interest inspired by strong challenge or satisfaction, curiosity or intention to accomplish fixed goals for green oriented tasks (Amabile, 1997;Birdi et al, 2016).…”
Section: Green Creativity Skillsmentioning
confidence: 99%
“…The Caffeine Research VAS displayed significant main effects in “alert” (p = 0.0005), “tired” (p = 0.0356), and “jittery” (p = 0.0044). Individuals who consumed Red Bull showed significant increases over baseline in “alert” and “jittery” and a significant decrease under baseline for “tired.” This pattern suggested that the consumption of energy drinks, such as Red Bull, may increase energetic arousal and may be correlated with decreased sadness shown in the study performed by Zabelina et al [ 19 ].…”
Section: Reviewmentioning
confidence: 71%
“…A more recent study by Zabelina et al evaluated the effects of caffeine on working memory and mood [ 19 ]. A total of 88 participants (60 females, 28 males; mean age = 21.6 years) were recruited into a randomized, double-blind, placebo-controlled study.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond depressants, caffeinated beverages have been suggested to improve creativity based on the link between caffeine and cognition [76]. Zabelina and Silvia [66] investigated the effect of moderate caffeine consumption on different measures of creativity (convergent and divergent thinking). The authors found that participants who took a 200 mg caffeine capsule had higher performance in a convergent thinking task (The Compound Remote Associates (CRA)), but no effect in a divergent thinking test was found (The Abbreviated Torrance Test for Adults (ATTA)).…”
Section: Gustatory Influences On Creativitymentioning
confidence: 99%